2003
DOI: 10.1021/bp0255917
|View full text |Cite
|
Sign up to set email alerts
|

Cell Growth Arrest by Nucleotides, Nucleosides and Bases as a Tool for Improved Production of Recombinant Proteins

Abstract: Arresting cell growth and thus decreasing cell division potentially lessens the chance for genetic drift in the cell population; this would be of utmost importance for the consistent production of biopharmaceuticals during long periods. The drawback of the addition of well-known synchronizing agents, such as chemotherapeutics, is that they cause a disproportionate accumulation of cellular constituents, leading to cell death. The use of compounds that are naturally synthesized by the cell, as is the case of nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 63 publications
(92 reference statements)
3
44
1
1
Order By: Relevance
“…2,4,5,23 Moreover, it has been reported that the cell cycles phase, specifically the percentage of cells in the G0/G1 phase, significantly influences the specific productivity and production of recombinant proteins in CHO cells. [16][17][18][19] Many researchers have focused on screening for chemicals that pause the cells in the G0/ G1 phase to enhance protein specific productivity in CHO cells. 16,24 Several tested chemicals had toxic effect on the cell growth and led to the decline of viable cell density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,5,23 Moreover, it has been reported that the cell cycles phase, specifically the percentage of cells in the G0/G1 phase, significantly influences the specific productivity and production of recombinant proteins in CHO cells. [16][17][18][19] Many researchers have focused on screening for chemicals that pause the cells in the G0/ G1 phase to enhance protein specific productivity in CHO cells. 16,24 Several tested chemicals had toxic effect on the cell growth and led to the decline of viable cell density.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] In addition, SFM formulae have been optimized to better support the physiology and metabolism of the cell and enhance target protein expression. [16][17][18] The aim of this study was to enhance the expression of rFVII by screening signal peptides and optimizing fed-batch media for efficient and long-term production. Five signal peptides from different sources were fused to the N-terminus of rFVII and its expression level during suspension culture was analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…These strategies have been divided by some authors (Carvalhal et al 2003) into four categories: (1) genetic, (2) environmental, (3) chemical, and (4) physical strategies. Although all these strategies may improve the protein production rate, addition of stimulatory agents is considered as a simple and low cost method, which could quickly impact on protein productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for obtaining synchronised populations of mammalian cells in vitro have been reported; genetic, chemical, environmental, and physical strategies have been used. 16,17 For reversible chemical synchronisation several compounds are available, as thymidine 18 for G1 phase synchronisation, mimosine 19 for late G1 phase synchronisation, aphidicolin, 20 rapamycine. 18 and hydroxyurea 21 for synchronisation at the G1/S transition phase, staurosporine 22 for G2 phase synchronisation and nocodazole 23 for synchronisation at the G2/M transition phase.…”
Section: Introductionmentioning
confidence: 99%